Application of The JMF 10 Warning Signs for Early Detection of Primary Immunodeficiency among Children with Recurrent Infections in Indonesia - Muktiarti, Dina; Hendarto, Aryono; Munasir, Zakiudin; Wulandari, Dewi; Satari, Hindra Irawan; Werdhani, Retno Asti; Wati, Ketut Dewi Kumara (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2025)
Introduction: Limited awareness and diagnostic resources contribute to delayed recognition of primary immunodeficiency (PID). The Jeffrey Modell Foundation (JMF) 10 warning signs have been widely used for screening. However, their diagnostic performance has not been validated in Indonesia. Objective: To evaluate the diagnostic performance of the JMF 10 warning signs for early detection of PID among children with recurrent infections in Indonesia. Methods: This multicentre cross-sectional study was conducted across 10 hospitals in Jakarta involving 254 children aged 0–18 years who met the severe, persistent, unusual, and recurrent (SPUR) infection criteria. The diagnosis of PID was established based on clinical diagnosis by the European Society for Immunodeficiencies (ESID) Registry Working Definitions. Analysis was performed to determine the sensitivity, specificity, predictive values, and accuracy of the JMF 10 warning signs. Results: Diagnostic performance for PID improved with the number of warning signs, with overall accuracy increasing from 15% (1 sign) to 86.2% (≥5 signs). A total score of ≥3 signs was associated with higher occurrence of PID (PR 2.63; 95% CI 1.23–5.60; p = 0.008), providing an optimal balance of 75.7% sensitivity and 48.9% specificity. The two most specific indicators were recurrent severe sinus infections (99.5%) and ear infections (95%). All PID subjects required IV antibiotics. Conclusion: The JMF warning signs remain a valuable clinical screening tool for early detection of PID among Indonesian children. A threshold of three or more warning signs provides reasonable accuracy for screening and referral of PID in resource-limited settings.